Reactive Astrocytes Contribute to Alzheimer’s Disease-Related Neurotoxicity and Synaptotoxicity in a Neuron-Astrocyte Co-culture Assay - Wasilewski, David; Villalba-Moreno, Nelson David; Stange, Inke; Glatzel, Markus; Sepulveda-Falla, Diego; Krasemann, Susanne (Frontiers in Cellular Neuroscience, 2022)
Pathological hallmarks of Alzheimer’s disease (AD) include deposition and accumulation of amyloid- β (Aβ), neurofibrillary tangle formation and neuronal loss. Pathogenesis of the presymptomatic disease stages remains elusive, although studies suggest that early structural and functional alterations likely occur at neuronal dendritic spines. Presymptomatic alterations may also affect different CNS cell types. However, specific contributions of these cell types as cause or consequence of pathology are difficult to study in vivo. There is a shortage of relatively simple, well-defined and validated in vitro models that allow a straightforward interpretation of results and recapitulate aspects of pathophysiology. For instance, dissecting AD-related processes (e.g. neurotoxicity versus synaptotoxicity) may be difficult with common cell-based systems such as neuronal cell lines or primary neurons. To investigate and characterize the impact of reactive astrocytes on neuronal morphology in the context of AD-related cues, we modified an in vitro co-culture assay of primary mouse neurons and primary mouse astrocytes, based on the so-called Banker „sandwich„ co-culture assay. Here we provide a simple and modular assay with fully differentiated primary mouse neurons to study paracrine interactions between neurons and astrocytes in the co-culture setting. Readouts were obtained from both cell types in our assay. Astrocyte feeders were pre-exposed to neuroinflammatory conditions by means of Aβ42, Aβ40, or LPS. Non-cell-autonomous toxic effects of reactive astrocytes on neurons were assessed using Sholl analysis to evaluate dendritic complexity, whereas synaptic puncta served as a readout of synaptotoxicity. Here we show that astrocytes actively contribute to the phenotype of primary neurons in an AD-specific context, emphasizing the role of different cell types in AD pathology. The cytokine expression pattern were significantly altered in treated astrocytes. Of note, the impact of reactive astrocytes on neurons was highly dependent of defined cell ratios. Our co-culture system is modular, of low-cost, and allows to probe aspects of neurodegeneration and neuroinflammation between two major CNS cell types, neurons and astrocytes, under well-defined experimental conditions. Our easy-to-follow protocol including work-flow figures may provide a methodological outline to study interactions of astrocytes and neurons also in the context of other diseases in the future.